Solar cell using spray casted Cs2SnI6 perovskite thin films on chemical bath deposited CdS yielding high open circuit voltage. (1st September 2020) - Amaya Suazo, Franco Josué; Shaji, Sadasivan; Avellaneda, David Avellaneda; Aguilar-Martínez, Josue Amilcar; Krishnan, Bindu
Graphical abstract: Highlights: Ambient stable Cs2 SnI6 double perovskite films by direct spray coating. Precursor solution containing CsI and SnI2 in non-stoichiometric ratio. Fabrication of ALL inorganic solar cell with structure Glass/FTO/CdS/Cs2 SnI6 /C/Ag. Voc = 0.86 V, the highest voltage ever known using this material. Abstract: In the present work, we report synthesis of Cs2 SnI6 double perovskite films by direct spray casting of precursor containing CsI and SnI2 dissolutions in DMF and the fabrication of solar cells using these films as absorber material. The films were prepared by varying the CsI: SnI2 molar ratio in the precursor, 2:1, 1:1, 1:2, 1:3 and 1:4. X-ray diffraction and Raman spectral analysis showed the formation of Cs2 SnI6 films with cubic structure when the precursor solution contained excess tin iodide. The optical band gap value of the films was 1.2–1.3 eV and the films were photoconductive. The stability studies established that the perovskite films were stable under ambient exposure. Further, we fabricated all-inorganic photovoltaic structures Glass/FTO/CdS/Cs2 SnI6 /C/Ag, using Cs2 SnI6 films formed at different conditions as absorber layer. Post thermal annealing of the PV devices at 150 °C showed the highest Voc = 0.86 V for this material. Thus, our results have demonstrated that spray deposition is a reproducible method to synthesize stable cesium tin iodide perovskite for applications in all inorganic p-n junction solar cells and other optoelectronic devices.